Evaluation of novel host markers detected in plasma and saliva as biosignatures for the rapid diagnosis of TB disease and monitoring of the response to TB treatment - Jacobs, Ruschca (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.